ESTETIKA IKLAN MODERN DI MEDIA MASSA CETAK INDONESIA:TINJAUAN PERSPEKTIFPOSTKOLONIAL - , KASIYAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This particular research aims at studying the postcolonial hegemony in modern advertising aesthetics representation of Indonesia printed mass media published. It in particular deals with: 1) the various sign system of postcolonial hegemony used